Safety assessment of selected medicinal food plants used in Ayurveda through CYP450 enzyme inhibition study. (9th May 2016) - Kar, Amit; Pandit, Subrata; Mukherjee, Kakali; Bahadur, Shiv; Mukherjee, Pulok K
Abstract: BACKGROUND: Andrographis paniculata, Bacopa monnieri and Centella asiatica are mentioned in Ayurveda for the management of neurodegenerative disorders. These plants and their phytomolecules, such as andrographolide, bacoside A and asiaticoside, were studied for their inhibition potential on pooled CYP450 as well as human CYP3A4, CYP2D6, CYP2C9 and CYP1A2 by CYP‐CO complex assay and fluorogenic assay respectively followed by IC50 determination. Quantification of bioactive compounds present in the extracts was done by RP‐HPLC. Heavy metal content in the selected medicinal plants was determined by atomic absorption spectroscopy. RESULT: CYP‐CO complex assay indicated significantly less inhibition potential than standard inhibitor ( P < 0.05 and above). A. paniculata showed highest inhibitory activity against CYP3A4 and CYP2D6 (IC50 = 63.06 ± 1.35 µg mL −1 ; 88.80 ± 3.32 µg mL −1 ), whereas C. asiatica and B. monnieri showed least inhibitory activity against CYP1A2 (IC50 = 288.83 ± 1.61 µg mL −1 ) and CYP2C9 (184.68 ± 3.79 µg mL −1 ), respectively. In all cases the extract showed higher inhibition than the single bioactive compounds. The heavy metals content in the plant extracts were within the permissible limits. CONCLUSION: The findings suggested that selected food plants and bioactive compounds contributed negligible interaction potential with CYP isozymes and may not possess any harmful effect with regard to their therapeutic application. © 2016 Society of Chemical Industry